2020
DOI: 10.4269/ajtmh.19-0816
|View full text |Cite
|
Sign up to set email alerts
|

Factors Determining Treatment Success in Children with Drug-Sensitive Tuberculosis in Ethiopia: A Three-Year Retrospective Analysis

Abstract: This study in the Amhara and Oromia regions of Ethiopia assessed the outcomes of tuberculosis (TB) treatment among children younger than 15 years. Retrospective data were collected on treatment outcomes and their determinants for children with TB for the cohorts of 2012-2014 enrolled in 40 hospitals and 137 health centers. Chi-square tests, t-tests, and logistic regression were used for the analysis. Of 2,557 children registered, 1,218 (47.6%) had clinically diagnosed pulmonary TB, 1,100 (43%) had extrapulmona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 12 publications
2
13
0
1
Order By: Relevance
“…Women are known to show better treatment outcomes as well as lower dropout rates and mortality. Seven other studies identified HIV status as a determinant of treatment outcomes (García-Basteiro et al, 2016;Habte et al, 2020;Khazaei et al, 2016;Ogbudebe et al, 2018;Oladimeji et al, 2021;Tesema et al, 2020;Umeokonkwo et al, 2020). Negative HIV status increases the likelihood of a successful treatment outcome.…”
Section: Internal Factorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Women are known to show better treatment outcomes as well as lower dropout rates and mortality. Seven other studies identified HIV status as a determinant of treatment outcomes (García-Basteiro et al, 2016;Habte et al, 2020;Khazaei et al, 2016;Ogbudebe et al, 2018;Oladimeji et al, 2021;Tesema et al, 2020;Umeokonkwo et al, 2020). Negative HIV status increases the likelihood of a successful treatment outcome.…”
Section: Internal Factorsmentioning
confidence: 99%
“…Internal factors consist of 11 determinants from within the TB patient, namely age, gender, education, HIV status, TB location, treatment category, alcohol consumption, drug use, smoking, type of ARB (Acid Resistant Bacteria), and comorbidities (Ahmad et al, 2020;Atif et al, 2014;Babalik et al, 2014;Banerjee et al, 2020;DesJardin et al, 2020;García-Basteiro et al, 2016;Habte et al, 2020;Khazaei et al, 2016;Mohammadzadeh et al, 2016;Mulogo et al, 2017;Muluye et al, 2018;Mundra et al, 2019;Ogbudebe et al, 2018;Oladimeji et al, 2021;Sadana et al, 2020;Sahyog et al, 2018;Son et al, 2021;Tesema et al, 2020;Tetteh et al, 2018;Umeokonkwo et al, 2020;Wen et al, 2018). 13 articles described age as an internal factor for TB treatment outcomes (Ahmad et al, 2020;Atif et al, 2014;Babalik et al, 2014;Habte et al, 2020;Mundra et al, 2019;Ogbudebe et al, 2018;Oladimeji et al, 2021;Sadana et al, 2020;Son et al, 2021;Tesema et al, 2020;Tetteh et al, 2018;Umeokonkwo et al, 2020;Wen et al, 2018). The likelihood of a successful treatment outcome was higher among patients aged 15-24 years, compared to patients younger than 14 years (Tesema et al, 2020), and over 61 years (Ahmad et al, 2020;Habte et al, 2020).…”
Section: Internal Factorsmentioning
confidence: 99%
See 3 more Smart Citations